2016
DOI: 10.14218/jcth.2015.00051
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus, Insulin Resistance, and Steatosis

Abstract: Hepatitis C virus (HCV) is one of the main causes of liver disease worldwide. Liver steatosis is a common finding in many hepatic and extrahepatic disorders, the most common being metabolic syndrome (MS). Over time, it has been shown that the frequent coexistence of these two conditions is not coincidental, since many epidemiological, clinical, and experimental studies have indicated HCV to be strongly associated with liver steatosis and numerous metabolic derangements. Here, we present an overview of publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 109 publications
0
42
0
4
Order By: Relevance
“…This is the case of neurodegenerative diseases, such as Alzheimer's disease (AD) (Kandimalla et al 2016), viral infections (Kralj et al 2016), Wolfram syndrome (Boutzios et al 2011) or some cancers (Klil-Drori et al 2016). Interestingly, ERmitochondria miscommunication has recently been suggested or reported in these pathologies.…”
Section: Er-mitochondria Miscommunication and Other Diseases Associatmentioning
confidence: 99%
“…This is the case of neurodegenerative diseases, such as Alzheimer's disease (AD) (Kandimalla et al 2016), viral infections (Kralj et al 2016), Wolfram syndrome (Boutzios et al 2011) or some cancers (Klil-Drori et al 2016). Interestingly, ERmitochondria miscommunication has recently been suggested or reported in these pathologies.…”
Section: Er-mitochondria Miscommunication and Other Diseases Associatmentioning
confidence: 99%
“…In the hepatocyte, HCV interferes with the lipid metabolism of the host to replicate and assemble leading to hepatic steatosis. The main mechanisms through which HCV leads to accumulation of triglycerides in the hepatocyte are the activation of lipogenesis, its impact on mitochondrial lipid oxidation, the lowering of microsomal triglyceride transfer protein activity, and the reduced activity of peroxisome proliferator activating receptor (PPAR) (4). The release of the virus from hepatocytes occurs by means of the very low-density lipoprotein (VLDL) (25).…”
Section: Discussionmentioning
confidence: 99%
“…ment of hepatic insulin-resistance in patients with HCV, both through a direct viral effect and through inflammatory cytokines: the inhibition of insulin receptor substrate (IRS), and the activation of suppressor of cytokine sing-align (SOCS) with inhibition of phosphatidylinositol 3 kinase-transducer, which has a key role in insulin metabolism (4). As far as the lipid metabolism is concerned, HCV relies on the host lipid metabolism to enter the hepatocytes and replicate, consequently impacting on the lipid metabolism itself (5).…”
mentioning
confidence: 99%
“…Other studies have also shown that HCV infection can cause insulin resistance by the phosphorylation of IRS-1 at a serine residue (Ser307) followed by a decreased phosphorylation of Akt Thr(308), Fox01 Ser(256) and GSK3β Ser(9), downstream players in the insulin signaling pathway[72,73]. These data raise the question whether insulin resistance is the cause of liver steatosis in patients with chronic HCV infection, or the consequence of viral molecular expression.…”
Section: Insulin Resistance and Hcv Infectionmentioning
confidence: 99%